Enhancing Creative Self-Efficacy through Creative Problem-Solving-Based E-Modules: An Effectiveness Study - Handini Asitha Putri; Rohati Rohati; Ade Kumalasari (MASI Mandiri Edukasi, 2025)
Improving students' creative self-efficacy is crucial in developing creative and innovative thinking skills. This study aims to see the effectiveness of creative problem-solving-based e-modules that support students' creative self-efficacy in straight-line equation material. This research applies the research and development method, which specifically adopts the ADDIE system development model, which consists of five sequential phases: Analysis, design, development, implementation, and evaluation. The research location coincided at SMP N 5 Jambi City, with students of class VIII B SMP N 5 Jambi City utilized as research subjects, with a research sample used as many as 30 people. In collecting data, researchers utilize a series of instruments, including a learner response questionnaire and a creative self-efficacy questionnaire that experts have validated. From the data analysis, a percentage score of 82.25% of “Highly Effective” was obtained from the survey results of students' responses and the analysis results of N-Gain of the creative self-efficacy questionnaire of 0.684. In line with these results, the gain value is equivalent to 68.4% for the interpretation category of gain effectiveness, indicating that the use of e-modules is in the “Moderately Effective” category. Therefore, this N-Gain number interprets that the creative problem-solving-based e-module that supports students' creative self-efficacy can be quite effective in teaching.